Characterization of erosion of gas pipelines by dry sand. Issue 1 (2nd January 2017) - Naz, M. Y.; Ismail, N. I.; Sulaiman, S. A.; Shukrullah, S.
ABSTRACT: In oil and gas industry, the economic considerations determine the selection of low cost materials, in general, carbon steel, for pipelines. However, another type of deformation that is not well understood is its erosion resistance. The objective of this study was to investigate the factors affecting the erosion of carbon steel in a dry sand stream. In this work, a laboratory built test rig was used to erode representative carbon steel plates with accelerated sand streams. The results revealed that the normal incidence sand stream of larger particles and higher impact velocities causes more erosion of the carbon steel. The highest erosion rate of 6.75 ± 0.16 was predicted at an impact angle of 90°, which was three times higher than the erosion rate at impact angle of 30°. Similarly, the erosion caused by the smaller particles was not as severe as the larger particles. The cross-section profiles revealed that the crater depth was increased from 7° to 32.8° with an increase in sand size from 200 µm to 600 µm. The deepest crater of 32.8° was induced by the largest sand size of 600 µm.